Pendampingan Implementasi Metode An Nahdliyah dalam Meningkatkan Kefasihan dan Ketepatan Tajwid Santri Madrasah Nurul Huda - Yogi Bagus Yudistira; Ummi Mufidatul Mahiroh; Siti Muwahidah Rodiyati; Muhammad Ilham Mahmudi; Syarip Hidayatulloh; Annisa Qothrunnada (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2026)
The low level of fluency and accuracy in the application of tajwid rules in Qur’anic recitation remains a significant issue at Madrasah Diniyah Nurul Huda, affecting students’ understanding and practice of Islamic teachings. This community service program aims to improve students’ Qur’anic reading skills through the implementation of the An-Nahdliyah method, which emphasizes tartil reading habits, guided classical instruction, rhythmic beat techniques, and tiered evaluation. The implementation method consists of initial observation, program planning, intensive instructional activities, mentoring, and evaluation. The results indicate a significant improvement in students’ ability to articulate makharijul huruf, apply tajwid rules accurately, and demonstrate increased confidence in Qur’anic recitation. In addition, the program contributes to strengthening the religious culture within the madrasah environment. The novelty of this program lies in the systematic integration of the An-Nahdliyah method within an intensive mentoring-based community service framework. The implications suggest that the An-Nahdliyah method can serve as an effective and practical model for Qur’anic learning and has the potential to be adopted in policies related to the development of religious education in madrasah diniyah.